Development of Competitiveness of Enterprise Structures under the Conditions of Accession of the Russian Federation to the WTO - SAMARINA, Evgeneya Alikovna; PETROVA, Anastasia Dmitrievna; BLAZHENKOVA, Natalia Mihailovna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article analyzes the diversification of the global economy, which had led to significant changes in the development of international relations that gave rise to a change in the political, social and legal processes in each country that actively participates in the market economy. In addition, the authors examined patterns and trends in the development of competitive abilities of small and medium enterprises under the influence of contemporary geopolitical realities. The analysis of the dynamics of the business entities based on statistical data serves as the methodology. The authors conclude that under the conditions of destabilization of the world economy, the Russian government assigns an important role to small and medium enterprises, which, thanks to their maneuverability, are better adapted to the constantly changing market conditions. Taking comprehensive and systematic measures to create an enabling environment, the state contributes to the competitive potential of the domestic small and medium enterprises that are able to compete with larger companies.
Keywords: Russian Federation; small and medium enterprises; competitiveness; the World Trade Organization